P045 TIGIT expression differentiates regulatory from inflammatory Th1* gut-homing effector CD4+ T cells in inflammatory bowel disease patients. (21st January 2022) - Heredia, M; Costes, L M M; Tindemans, I; Aardoom, M A; Klomberg, R C W; Kemos, P; Joosse, M E; van Haaften, D H; Tuk, B; Ruemmele, F; Croft, N M; Escher, J C; et al.
Abstract: Background: Crohn's disease (CD) and ulcerative colitis (UC) are characterized by intestinal infiltration of pathogenic effector CD4 + T cells. The defects driving loss of T-cell regulation vary between patients and remain undefined. Previously, we have shown that in human intestine, 20–40% of effector (CD62L neg CD4 + ) T cells express TIGIT (T cell immunoglobulin and ITIM domain), an inhibitory receptor modulating dendritic cell and T-cell function. TIGIT expression is enriched in circulating gut-homing CD38 + effector T cells in healthy controls while in a subgroup of IBD patients with active intestinal inflammation, frequencies of inhibitory TIGIT + CD38 + effector T cells are decreased and associated with earlier relapse of disease. Here we hypothesized that gut-homing effector T cells lacking TIGIT (TIGIT neg ) are pathogenic mediators of intestinal inflammation in IBD and assessed whether patients with low frequencies have a distinctive disease immunotype. Methods: In the Rotterdam PIBD-SETQuality cohort of newly diagnosed pediatric IBD patients (CD: n=50; UC: n=25), patients with suspicion of IBD but negative diagnosis (n=17) and age-matched healthy controls (HC: n=22), we monitored TIGIT + and TIGIT neg CD38 + effector T cells in peripheral blood, collected plasma at diagnosis and during therapy and phenotyped intestinal T cells. Results: At diagnosis, 50% of CD patients had strongly reduced frequencies of inhibitory TIGIT + CD38 + effector T cells compared to UC patients and HC. CD patients with reduced frequencies of inhibitory TIGIT + CD38 + effector T cells had higher plasma IFN-γ concentrations and 53% of them experienced a disease relapse by 1 year versus 25% for CD patients with normal TIGIT + CD38 + effector frequencies. In keeping with our hypothesis that TIGIT neg gut-homing effector T cells are pathogenic, absence of TIGIT expression identified CD38 + effector T cells enriched in recent proliferation and having high expression of chemokine receptors associated with inflammatory non-classical T helper-1 IFNγ  high IL-17A low producing (Th1*) cells. Moreover, intestinal TIGIT neg CD4 + T cells of CD patients contained higher frequencies of IFNγ and IL-17A producing cells than TIGIT + CD4 + T cells. In order to identify the factors that drive differentiation of the pathogenic Th1* cells, inhibitory TIGIT + CD38 + effector T cells from HC were exposed to an array of IBD-associated cytokines in vitro. Only IL-12p70, a known driver of IFNγ, could convert inhibitory TIGIT + CD38 + effector T cells into their TIGIT neg proinflammatory counterpart. Conclusion: We identify TIGIT neg gut-homing effector T cells, enriched in Th1* cells, as potential drivers of intestinal inflammation in a subgroup of CD, but not UC patients, with a more severe disease course.